Koherensi dan Kejelasan Kalimat dalam Surat Perjanjian Kerjasama: Pendekatan Linguistik dan Legal - Septiani, Sasi; Ramadhany, Chusnul Lintang; Putri, Synta Aulia; Anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to analyze linguistic aspects in cooperation agreement letters, particularly the use of legal terms, sentence coherence, and emphasis through linguistic elements such as bolding and quotation marks. Data were collected from several cooperation agreements in the health sector and analyzed using a qualitative descriptive approach. The results show that legal terms such as "First Party," "Second Party," as well as Force Majeure and breach of contract clauses must be consistently structured to ensure legal certainty and prevent misinterpretation. The use of linguistic elements such as conditional sentences, bolding, and quotation marks helps clarify meaning and strengthen the message in the document. Moreover, this research affirms that linguistic aspects play a significant role in supporting the clarity and readability of legal documents, which has implications for law enforcement and reducing the risk of disputes. The recommendation from this research is the need for a balance between linguistic and legal approaches in drafting cooperation agreements to make documents more effective and legally valid